2006
DOI: 10.1016/j.jfa.2006.03.004
|View full text |Cite
|
Sign up to set email alerts
|

A characteristic operator function for the class of n-hypercontractions

Abstract: We consider a class of bounded linear operators on Hilbert space called n-hypercontractions which relates naturally to adjoint shift operators on certain vector-valued standard weighted Bergman spaces on the unit disc. In the context of n-hypercontractions in the class C 0· we introduce a counterpart to the so-called characteristic operator function for a contraction operator. This generalized characteristic operator function W n,T is an operator-valued analytic function in the unit disc whose values are opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 21 publications
5
28
0
Order By: Relevance
“…We note that the last statement in the theorem is a consequence of part (2b) of Lemma 6.1. We also note that realization formula (7.40) appears in [27,29]) in slightly different terms. 7.5.…”
Section: Beurling-lax Theorem For a Nmentioning
confidence: 89%
See 2 more Smart Citations
“…We note that the last statement in the theorem is a consequence of part (2b) of Lemma 6.1. We also note that realization formula (7.40) appears in [27,29]) in slightly different terms. 7.5.…”
Section: Beurling-lax Theorem For a Nmentioning
confidence: 89%
“…In the quest for a parallel system-theoretic interpretation for Bergman inner functions on the unit disk, Olofsson [27,29] has shown that realization formulas of the type Θ(z) = D + zCR n (zA)B involving higher-order resolvents R n (zA) arise naturally and he also associated a certain higher-order time-invariant linear system having such a Θ(z) as transfer function. We shall see below that functions of the form Θ(z) = D + zCR n,k (zA)B involving shifted higher-order resolvents R n,k (zA) also arise naturally.…”
Section: System Theory Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…We mention that for n = α + 2 positive integer the result of Theorem 1.4 originates from [18,Section 1] where it was used in a calculation of operator-valued Bergman inner functions.…”
Section: The Operator Identitymentioning
confidence: 99%
“…Recently, biharmonic Bergman space potential theory has been applied by Hedenmalm, Shimorin and others in the study of Hele-Shaw flows and related problems of differential geometric nature (see [8,9,10]). In recent work the author has indicated how related methods can be used to develop a generalized systems theory for weighted Bergman space norms (see [16,17,18]). …”
Section: Introductionmentioning
confidence: 99%